Finding Potential Source of Cold-Active Xylanase - Malik, S. M.; Ahanger, F. A.; Wani, N.; Sahay, S.; Jain, K. (International Journal of Scientific Research in Biological Sciences, 2018)
Xylanases are glycosidases that catalyze the endohydrolysis of 1,4-β-D-xylosidic linkages in xylan, the main constituent of hemicelluloses found in plant cell wall. Xylanases encompass great industrial potential, and their cold-active counterparts have even more than that. Accordingly, three cold-active fungi, Penicillium canesence (BPF4), Truncatella angustata (BPF5), and Pseudogymnoascus roseus (BPF6) available as laboratory stocks have been screened for their ability to produce extracellular xylanases at cold temperature. The selection of hyper producing strains of xylanase was carried out on Potato Dextrose Agar (PDA) medium fortified with 1% (w/v) of xylan incubated at 20oC for seven days. Selection for best producer of xylanase was done on the basis of breadth of clear zones observed after flooding the plates with Gram’s iodine indicating the hydrolysis of xylan by xylanase around the colonies. The fungus T. angustata was found to produce the highest amount of xylanase followed by Pseu. roseus and P. canesence in that order. The cold-active xylanase-secreting ability of the fungal species was verified by incubating them in xylanase producing medium at 20oC. Consequently, T. angustata, Pseu. roseus and P. canesence were found to produce xylanase activity equal to 11.0 IU/ml, 7.0 IU/ml and 5.9 IU/ml respectively. This is the first report of the fungus T. angustata having cold-active xylanases producing ability.